2021
DOI: 10.1017/s0007114521002877
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean diet and physical activity: better together than apart for the prevention of premature mortality

Abstract: Diet and physical activity (PA) have been studied extensively in epidemiology as single or combined lifestyle factors; however, their interaction has not been studied thoroughly. Studying potential synergisms between lifestyle components with a comprehensive interaction analysis, including additive measures of interaction, provides key insights into the nature of their joint effect and helps target interventions more effectively. First, a comprehensive review was conducted to assess the potential research gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…This fact is also consistent with the recommendation of meeting with 24-h movement guidelines [ 1 , 2 ], since the current evidence suggests that these guidelines may have essential implications for health and are linked with several desirable health outcomes in young [ 65 ] and adult populations [ 6 , 7 ]. Based on the low levels of the young population meeting the 24-h movement guidelines as well as low adherence to the MedDiet (especially in this region of Spain [ 45 ]), it is clear that knowledge, awareness, and implementation of these healthy behaviors by the general population need to be improved in combination with one another for their potential synergistic effect [ 4 , 10 , 28 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…This fact is also consistent with the recommendation of meeting with 24-h movement guidelines [ 1 , 2 ], since the current evidence suggests that these guidelines may have essential implications for health and are linked with several desirable health outcomes in young [ 65 ] and adult populations [ 6 , 7 ]. Based on the low levels of the young population meeting the 24-h movement guidelines as well as low adherence to the MedDiet (especially in this region of Spain [ 45 ]), it is clear that knowledge, awareness, and implementation of these healthy behaviors by the general population need to be improved in combination with one another for their potential synergistic effect [ 4 , 10 , 28 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants who adhere to a MedDiet are often more likely to be physically active (Alvarez-Alvarez et al, 2018;Bizzozero-Peroni, 2022). The interaction between MedDiet and physical activity has been highlighted as significant in reducing overall mortality (Alvarez-Alvarez et al, 2018;Hershey et al, 2022), suggesting it is important to look at interaction effects in outcomes such as AD and cerebrovascular disease. Poor sleep quality has been associated with higher risk for AD (Minakawa et al, 2019), with adherence to the MedDiet associated with better sleep quality (Zuraikat et al, 2020), suggesting a possible intervention opportunity to reduce AD risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, comprehensive evidence of literature underlined how a combination of dietary and physical activity interventions would have a higher impact on health and body weight [ 239 ]. Furthermore, some studies suggested a joint synergistic effect on mortality risk of higher adherence to specifically Mediterranean diet and high physical activity addressing the current research gap regarding interaction analyses regarding these two variables [ 240 ].…”
Section: Underrated Aspects Of the Mediterranean Dietmentioning
confidence: 99%